ANALYSIS OF THE EFFECT OF AGING TIME ON AMORPHOUS PHASE NANOSILICA FROM PARANGLOE IGNEOUS ROCKS USING THE SOL-GEL METHOD - Rismawati Rismawati; Ahmad Fudhail Majid; Suriati Eka Putri (Analit : Analytical and Environmental Chemistry, 2024)
In this research, an analysis of the effect of aging time on amorphous phase nanosilica from Parangloeigneous rock was conducted using the sol-gel method. The research samples were taken from aroundthe Parangloe waterfall in Gowa regency, South Sulawesi province. The research stages includedsample preparation, nanosilica synthesis using the sol-gel method, and synthesis resultscharacterization. Characterization was performed using XRF, XRD, SEM-EDX, and PSA. XRF datashowed that the silica content was 53.62% in the form of white powder, and after synthesis, itdecreased to 12.38%. SEM-EDX testing results showed small agglomerated spheres with an EDX of4.52%. A 3-hour aging time variation resulted in an amorphous phase, making 3 hours the optimumtime for amorphous phase nanosilica formation with the highest peak intensity at 2Î¸=25.42 ° and aparticle size of 170.8 nm.